Fatigue assessment of multilayer coatings using lock-in thermography. (5th March 2018) - Laborda, Andreu; Robinson, Andrew; Wang, Shuncai; Zhang, Yi; Reed, Philippa
Abstract: Plain bearings experience cyclic loading during operation, which may cause fatigue failure. In the bearings under study a steel backing has a leaded bronze interlayer, covered by a thin (20 μm) multilayer coating, which consists of several electroplated layers composed of Sn, Ni and Cu. Commercial performance assessments simulate the conditions of engines in a 'Pass or Fail' test. A new methodology is proposed to assess the fundamental fatigue behaviour for such complex layered bearings. Accelerated fatigue tests on half-shell bearings have been conducted under 3-point bend, whilst the coated side of the bearings are recorded with an infrared camera. Cyclic tests with strain gauges placed on the coating have been performed to evaluate the strains developing during loading. By combining these tests we can rank different coatings. A compliance based failure criterion is also compared with a failure criterion based on early damage revealed by infrared thermography, showing that the latter is far less conservative. Thus, this methodology allows detection of small scale fatigue cracks in the coatings significantly earlier, facilitating assessment and identification of possible mechanisms to explain the differences in fatigue performance between coatings. This provides valuable information to develop new coatings for future bearing designs. Graphical abstract: Image 1 Highlights: The use of Infrared Thermography allows ranking of the fatigue performance of multilayer coatings during fatigue tests. The new methodology detects damage earlier than other methodologies, facilitating far less conservative failure criteria. The coating with two intermetallic layers (2IML) shows better fatigue performance than the coatings with 1IML and 3IML.